Implementation of the Book Durus Al Lughoh Al Arabiyyah on the Modern Method of Language Skills Development at Nurul Jadid Islamic Boarding School Paiton Probolinggo: تنفيذ كتاب دروس اللغة العربية على الطريقة الحديثة لتنمية المهارات اللغوية في معهد نور الجديد الإسلامي بيطان برابالنجا - Rosyidatul Khoiriyah; Abdul Hafidz Zaid (Postgraduate Study Programme of Universitas Islam Negeri KH. Achmad Siddiq Jember, Indonesia., 2022)
Arabic language skills (listening, speaking, reading, and writing) form the basis of teaching and learning in each phase of learning Arabic. The aim is to establish a language environment and good character in life. The purpose of Durus al-Lughoh al-Arabiya ‘ala at-Tariqah al-Hadith is to be able to master language skills well for beginner language learners. And in the process of teaching this book, the instructor must teach this book with a modern method that is not translating the meaning of vocabulary or sentences into the mother tongue either verbally or in writing. In this case, the researchers conducted research in the application of the book Durus al-Lughoh al-Arabiya ‘ala at-Thariqah al-Haditsah to improve the Arabic language skills of the students of the Islamic Boarding School Nurul Jadid Paiton Probolinggo. And the method used in this study is the experimental method of forming two learning groups, one group as the control class and the other as the experimental class. The results of this study are the teaching of Arabic using the book Durus al-Lughoh al-Arabiya ‘ala at-Thariqah al-Haditsah to improve the Arabic language skills of students of the Islamic Boarding School Nurul Jadid Paiton Probolinggo.